Peningkatan Self Concept Siswa Sekolah Dasar Melalui Teknik Scaffolding - Takaria, Johannis - (Jurnal Bimbingan dan Konseling Terapan, 2019)
AbstractThe purpose of the study was to analyze the differences in the increase in self-concept of elementary school students through scaffolding techniques in Saparua District, Central Maluku Regency, Maluku Province. The method used was a quasi-experimental design with one group pretest-posttest and involved 30 elementary school students as research samples. The test uses paired sample t-test and it is identified that there are differences in students' self concepts before and after scaffolding techniques are applied. Self-concept enhancement was analyzed using N-gain, where each self-concept indicator achieved an increase in the medium category. The indicators of attitude and self-confidence increased by 31%, The indicators of View of ability and disability increased by 43%, and indicators of self-sensitivity increased by 52%, and the indicators of views of others towards themselves was 45%. These result are due to the effectiveness of scaffolding, because by scaffolding students can be helped to solve a problem.